Aetiological, seasonal and antibiotic susceptibility patterns of diarrhoeal diseases in Bhutan (2016–2022): a retrospective study of surveillance data - Sangay Dorji; Kinley Gyem; Sonam Pelden; Dorji Tshering; Kinley Penjor; Rinzin Wangchuk; Jigme Tenzin; Birdi Lal Phuyel (BMJ Open)
Objectives This study aimed to identify the aetiological spectrum, seasonal distribution and antimicrobial resistance patterns of diarrhoeal diseases in Bhutan.Study design and setting The study used a cross-sectional, retrospective analysis of secondary data gathered through a passive, hospital-based sentinel surveillance for diarrhoeal disease across 12 hospitals, representing Bhutan’s demographically diverse regions.Participants A total of 3429 participants’ data of all age groups who presented with diarrhoea at sentinel hospitals between 1 January 1 2016 and 31 December 2022 were analysed.Results Diarrhoeagenic Escherichia coli (DEC), Shigella, Salmonella and Aeromonas spp. were predominant bacterial pathogens, while Rotavirus, Astrovirus and Norovirus were the leading viral pathogens. Coinfections were observed in 195 cases. Children under nine were significantly affected than the other age groups. Seasonal trends revealed that bacterial pathogen incidence peaked during the summer/monsoon season, viral pathogens were more common in winter and spring, and parasites persisted year-round. Among the antibiotics tested, gentamicin, chloramphenicol, ceftriaxone and tetracycline exhibited high efficacy, with susceptibility rates of 93.4%, 87.2%, 81.5% and 69.5%, respectively. Conversely, high resistance rates were observed for amoxicillin (80.3%), ampicillin (77.4%) and nalidixic acid (69.5%). Multidrug resistance was prevalent, with β-lactamase production contributing to resistance rates of 80.7% to penicillin and 65.4% to fluoroquinolones groups. Cephalosporin resistance was also notable, with rates of 34.4% for cephalexin, 40.0% for cefazolin and 16.9% for ceftriaxone.Conclusions DEC and Rotavirus were identified as the leading causes of diarrhoea, with significant resistance patterns observed in common bacterial isolates. These findings underscore the need for DEC screening in paediatric cases and emphasise the need for sustained antimicrobial resistance surveillance.